Neodothiora pruni sp. nov., a Biosurfactant-Producing Ascomycetous Yeast Species Isolated from Flower of Prunus mume - Jeong-Seon Kim; Miran Lee; Jun Heo; Soon-Wo Kwon; Bong-Sik Yun; Yiseul Kim (Mycobiology)
A yeast strain, designated as JAF-11T, was isolated from flower of Prunus mume Sieb. et Zucc. in Gwangyang, Republic of Korea. Phylogenetic analysis showed that strain JAF-11T was closely related to Neodothiora populina CPC 39399T with 2.07 % sequence divergence (12 nucleotide substitutions and three gaps in 581 nucleotides) in the D1/D2 domain of the large subunit (LSU) rRNA gene, and Rhizosphaera macrospora CBS 208.79T with 4.66 % sequence divergence (25 nucleotide substitutions and five gaps in 535 nucleotides) in the internal transcribed spacer (ITS) region. Further analysis based on the concatenated sequences of the D1/D2 domain of the LSU rRNA gene and the ITS region confirmed that strain JAF-11T was well-separated from Neodothiora populina CPC 39399T. In addition to the phylogenetic differences, strain JAF-11T was distinguished from its closest species, Neodothiora populina CPC 39399T and Rhizosphaera macrospora CBS 208.79T belonging to the family Dothioraceae by its phenotypic characteristics, such as assimilation of carbon sources. Hence, the name Neodothiora pruni sp. nov. is proposed with type strain JAF-11T (KACC 48808T; MB 850034).